PENTINGNYA PEMILIHAN Peer Group DALAM PENCEGAHAN PENYALAHGUNAAN NAPZA DI KALANGAN PELAJAR SMA 14 MAKASSAR - Waode Rustiah; Muawanah Muawanah; Dewi Arisanti; Mujahidah Basarang; Anita Anita; Nurul Ni’ma Azis (Lontara Abdimas : Jurnal Pengabdian Kepada Masyarakat, 2023)
This Community Service Program aims to provide knowledge about the importance of selecting Peer Groups in preventing drug abuse among students of SMA 14 Makassar. Drug abuse is so dangerous because it can form pathological behavior and is usually carried out by individuals who have a vulnerable personality or have a high risk, and if done for a certain period of time will cause bio-psycho-social-spiritual disturbances. This community service implementation method consists of two stages, namely: 1) Distribution of extension materials; 2) Presentation of material and providing education with the lecture method; 3) Provide feedback as an evaluation to determine student understanding of the material presented. The results show that this counseling provides additional knowledge about the importance of the peer group approach. The Peer Group approach in preventing drug abuse is carried out so that the peer group that is formed in adolescents has an understanding of the dangers of drugs and will influence their peer group to avoid drug abuse. The main purpose of forming a peer group is to keep youth away from drug abuse. The vulnerability of adolescents is trapped in a negative peer group, because at that time they experience a crisis of identity, "who am I". Therefore, there is a need for adolescents to form their identity as "who" or "as" what. If they are facilitated or intervened to be involved in positive and interested activities, then this will really help youth to find their identity and also get support or reinforcement from the group. At the end of this activity, small groups of 7-10 people were formed based on their interests and talents, a leader was determined and they were asked to discuss the activities they would carry out in the future. The results of the discussion are then conveyed to the school and other parties who can assist in implementing the group activities so that they become positive activities